PEMANTAU CURAH HUJAN, SUHU DAN KELEMBABAN UDARA MELALUI WEB BERBASIS MIKROKONTROLLER ARDUINO - , FAJAR SETIAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final project goals is to design a tool for monitoring rainfall, temperature and humidity whichâs can be viewed through the webpage. This tool will make it easier people to know the weather conditions in other area or place where they headed in real time remotely simply by accessing the website address is provided. Tool is still a prototype with a single node is expected later it contained many nodes are connected to the web server, using either a wired or wireless. After Testing The accuracy is quite good proximate 95%.